Tin-lead perovskite solar cell without stannous fluoride and preparation method thereof
By using stannous fluoride-free and lead fluoride as surface passivating agents in tin-lead perovskite solar cells, the deprotonation reaction and corrosive reaction problems caused by stannous fluoride are solved, and the photothermal stability and carrier extraction rate of the battery are significantly improved.
Patent Information
- Application Number
- CN202411902743.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The stannous fluoride additive in tin-lead perovskite solar cells will lead to the deprotonation reaction and the generation of corrosive reaction products under photothermal conditions, limiting the photothermal stability of the cell.
The preparation method of tin lead perovskite solar cell without stannous fluoride is adopted. By using lead fluoride as a surface passivator in the tin lead perovskite film, it replaces the stannous fluoride additive in the precursor liquid to avoid the occurrence of deprotonation and corrosive reactions.
The photothermal stability of tin-lead perovskite solar cells is significantly improved, the perovskite degradation caused by stannous fluoride and the generation of corrosive products is avoided, and the formation of tetravalent tin and tin vacancy defects in the film is inhibited.
Smart Images

Figure CN119630249A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tin-lead perovskite solar cells, and in particular to a high-quality tin-lead perovskite film without stannous fluoride additives and a preparation method thereof. Background Art
[0002] Tin-lead perovskite cells have the highest theoretical limit efficiency of a single cell, but the current device has poor photothermal stability, which limits its application prospects. Stannous fluoride additives can inhibit the generation of tetravalent tin and tin vacancies, and are an indispensable component in high-efficiency tin-lead perovskite cells. However, stannous fluoride will undergo severe deprotonation reactions with perovskite components under heating or light conditions, producing a large number of formamidine vacancy defects and unfavorable band bending; at the same time, the deprotonation product-hydrofluoric acid is highly corrosive and has a significant corrosive effect on both ITO anodes and metal cathodes. Therefore, if the stannous fluoride additive can be replaced to avoid the deprotonation reaction and the generation of corrosive reaction products under photothermal conditions, while not affecting the film crystal quality and the generation of tetravalent tin / tin vacancies, the photothermal stability can be significantly improved without reducing the photoelectric conversion efficiency of tin-lead perovskite cells. Summary of the invention
[0003] Based on this, the purpose of the present invention is to provide a stannous fluoride-free, low-defect tin-lead perovskite solar cell and a preparation method to address the problem of the limitation of stannous fluoride additives in tin-lead perovskite on photothermal stability. The method can not only inhibit the formation of tetravalent tin and tin vacancies, but also avoid the deprotonation degradation reaction under photothermal conditions. The method can be applied in perovskite cells to significantly improve their photothermal stability.
[0004] The specific technical solution for achieving the purpose of the present invention is:
[0005] A method for preparing a tin-lead perovskite solar cell without stannous fluoride, the preparation method comprising the following steps:
[0006] Step 1: Select a substrate, first use a cleaning agent to ultrasonically clean it for 10-30 minutes to remove surface grease and organic matter, then use deionized water, acetone, and isopropanol to ultrasonically clean it for 10-30 minutes each, blow dry it with nitrogen, and then treat it with ozone plasma for 15-30 minutes before use;
[0007] Step 2: On the treated substrate, a hole transport layer is deposited by solution spin coating. The hole transport layer is a P3CT-Cs material layer, which is formed by spin coating a methanol solution of P3CT-Cs with a concentration of 0.2-1.0 mg / ml. The speed of the coating machine is 2000-5000 rpm, the time is 30-60 seconds, and the thickness is 5-10 nm.
[0008] Step 3: Preparing a tin-lead perovskite thin film layer on the hole transport layer, specifically:
[0009] 3.1: Prepare the tin-lead perovskite precursor solution: dissolve 1.20-1.30 mmol FAI, 0.30-0.45 mmol CsI, 0.75-0.90 mmol SnI2, 0.75-0.90 mmol PbI2 and 0.02-0.05 mmol GuaSCN in a mixed solvent of 600 μl N,N-dimethylamine and 200 μl dimethyl sulfoxide, add 20-60 mg metal lead powder, and stir at room temperature overnight;
[0010] 3.2: Deposit the tin-lead perovskite precursor solution on the P3CT-Cs hole transport layer by solution spin coating, with the rotation speed first being 800-1500 rpm for 5-15 seconds, then 3500-5000 rpm for 40-70 seconds, and dropping 200-400 μL of chlorobenzene antisolvent between 5-10 seconds after the second rotation speed ends;
[0011] Then annealing at 110-130°C for 10-15 minutes to form a tin-lead perovskite film;
[0012] 3.3 The tin-lead perovskite film is subjected to surface passivation post-treatment, wherein a 0.5-1.5 mg / ml anhydrous isopropanol solution of a metal lead salt surface passivator is deposited on the tin-lead perovskite film by spin coating at a rotation speed of 4000-5000 rpm for 20-30 seconds, and then annealed at 90-100°C for 3-5 minutes; the metal lead salt is one of lead fluoride, lead bromide, lead chloride and lead oxalate;
[0013] Step 4: an electron transport layer is formed on the post-treated tin-lead perovskite thin film layer, a C60 layer with a thickness of 20-40 nm is deposited by vacuum evaporation, and then a BCP layer with a thickness of 5-8 nm is deposited on the C60 layer by vacuum evaporation, and a LiF layer with a thickness of 1-3 nm is deposited on the BCP layer by vacuum evaporation;
[0014] Step 5: depositing a layer of silver as an electrode on the electron transport layer by vacuum evaporation, with a thickness of 80-150 nm; and obtaining the tin-lead perovskite solar cell without stannous fluoride.
[0015] A tin-lead perovskite solar cell without stannous fluoride prepared based on the above method, wherein the tin-lead perovskite film layer does not contain stannous fluoride additives, reduces film defects and improves carrier extraction rate through chemical passivation and field effect passivation of a surface passivator; the surface passivator forms stable ionic bonds and interface dipole effects with the surface of the tin-lead perovskite film, thereby ensuring the durability of the battery under light and heat conditions.
[0016] The tin-lead perovskite battery of the present invention is characterized in that the stannous fluoride additive in the precursor solution is replaced by lead fluoride post-treatment. Within the battery operating temperature, the lead fluoride is not easy to undergo a deprotonation reaction of the organic amine component, thereby avoiding the degradation of the perovskite caused by the deprotonation reaction between the stannous fluoride and the organic amine, while avoiding the generation of corrosive products, and effectively inhibiting the generation of tetravalent tin and tin vacancy defects in the film.
[0017] The present invention relates to a tin-lead perovskite solar cell and a preparation method thereof. A surface passivator is introduced into the perovskite layer of the tin-lead perovskite solar cell, which is one or more metal salts such as lead fluoride, lead bromide, lead chloride, and lead oxalate. The surface passivation strategy is applied to the tin-lead perovskite solar cell, which can avoid the dependence of the high-efficiency tin-lead perovskite solar cell on the stannous fluoride additive, inhibit the perovskite deprotonation reaction caused by stannous fluoride, and thus effectively improve the light and thermal stability of the tin-lead perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a schematic diagram of the structure of the tin-lead perovskite solar cell of the present invention;
[0019] Figure 2 Schematic diagram of thermal stability of perovskite films containing stannous fluoride additive and lead fluoride passivator;
[0020] Figure 3 Schematic diagram of the energy band structure change of the perovskite film containing stannous fluoride additive and lead fluoride passivator before and after degradation;
[0021] Figure 4 Schematic diagram of carrier transport performance of the control group of the present invention, the tin-lead perovskite battery containing stannous fluoride additive and lead fluoride passivator;
[0022] Figure 5 Schematic diagram of IV curve and photothermal stability of tin-lead perovskite battery of the control group of the present invention and tin-lead perovskite battery with lead fluoride passivation agent. DETAILED DESCRIPTION
[0023] The tin-lead perovskite solar cell and its preparation method provided by the present invention are described in detail below.
[0024] The tin-lead perovskite precursor solution provided by the present invention does not contain stannous fluoride additive, and is replaced by a lead salt surface passivator.
[0025] The concentration of the lead salt surface passivator solution is 0.5-3.0 mg / ml. When used in perovskite solar cells, considering the improvement effect of the post-treatment material on the efficiency and stability of the cell, preferably, the concentration of the post-treatment material is 0.5-1.5 mg / ml.
[0026] In the ABX3 type organic-inorganic hybrid perovskite material, A is an organic amine cation or a metal cesium cation, and B is Pb 2+ Sn 2+ ,Ge 2+ Cation, X is a halogen anion or SCN - Anion. Preferably, A is CH3NH3 + 、HC(NH2) 2+ and Cs + , B is Pb 2+ and Sn 2+ , X is I - Since the perovskite band gap is 1.22 eV when the molar ratio of tin to lead is 1:1, it has the highest theoretical efficiency of a single cell. Therefore, the tin-lead perovskite material is further preferably Cs 0.2 FA 0.8 Pb 0.5 Sn 0.5 I3.
[0027] The surface passivator is one or more of metal lead salts such as lead fluoride, lead bromide, lead chloride, and lead oxalate. Since lead fluoride has better solubility in perovskite antisolvents such as isopropanol, it is easy to achieve selective regulation and solution preparation. In addition, fluoride ions can effectively inhibit the formation of tetravalent tin and tin vacancy defects on the surface of the film, which is beneficial to the improvement of battery efficiency. Therefore, the surface passivator is preferably lead fluoride.
[0028] See also Figure 1 The tin-lead perovskite solar cell of the present invention comprises a stacked substrate 1, a hole transport layer 2, a tin-lead perovskite film 3, an electron transport layer 4 and a metal electrode 5.
[0029] The material of the substrate 1 is not limited, and can be any one of glass, silicon wafer, and stainless steel sheet. ITO is a metal compound with high visible spectrum transmittance and excellent electrical conductivity, so the substrate 1 is preferably ITO conductive glass.
[0030] The hole transport layer 2 is a poly[3-(cesium butyrate)thiophene] (P3CT-Cs) material layer with a thickness of 5-15 nm. Compared with the commonly used PEDOT:PSS hole transport layer (highest occupied orbital energy level HOMO = -5.0 eV), the HOMO energy level of P3CT-Cs is -5.08 eV, which is closer to the valence band (-5.31 eV) of the prepared tin-lead perovskite, and can effectively avoid energy loss caused by energy level mismatch. The preferred thickness of P3CT-Cs is 8 nm, and the chemical structure is as follows:
[0031]
[0032] The tin-lead perovskite film 3 has no stannous fluoride additive in its precursor solution. The film is formed by solution spin coating combined with anti-solvent extraction. Considering the effect of the thickness of the perovskite layer on light absorption and bulk phase recombination, the preferred thickness is 800-1300 nm.
[0033] The tin-lead perovskite film is post-treated. Considering the passivation effect of fluoride ions on tetravalent tin and tin vacancy defects, and the strong binding effect of lead ions and fluoride ions to avoid the deprotonation reaction of fluoride ions and organic ammonium salts, lead fluoride is preferably used for post-treatment of the perovskite film. Considering that solution spin coating is easy to implement, solution spin coating is preferred. Considering that isopropanol has good solubility for lead fluoride and will not damage the underlying perovskite, the preferred solvent is isopropanol. Too high a concentration of lead fluoride will affect carrier transport, and too low a concentration will not have a significant defect passivation effect, so the preferred concentration is 0.5-1.5 mg / ml.
[0034] The electron transport layer 4 includes a C60 layer and a BCP layer stacked in sequence, the thickness of the C60 layer is 30-40 nm, the thickness of the BCP layer is 6-10 nm, the thickness of the LiF layer is 1-3 nm, and the thickness of the electron transport layer 4 is 37-53 nm. The C60, BCP and LiF layers are all prepared by vacuum evaporation, which can ensure that the film is more dense and uniform, and the preferred thicknesses are 30 nm, 6 nm and 1 nm, respectively.
[0035] The thickness of the electrode 5 is 100-300 nm, and the material is not limited. However, considering the cost and work function of the metal, the electrode is preferably a silver electrode, and the preferred thickness is 100 nm.
[0036] Hereinafter, the tin-lead perovskite film, the tin-lead perovskite battery and the preparation method thereof will be further described through specific examples.
[0037] Example
[0038] like Figure 1 As shown, the tin-lead perovskite solar cell includes a substrate 1, a hole transport layer 2, a tin-lead perovskite film 3, a surface passivation layer 4, an electron transport layer 5 and a metal electrode 6 which are stacked in sequence, and the preparation method is as follows:
[0039] Using ITO conductive glass as substrate 1, first use ITO cleaning agent to ultrasonically clean for 15 minutes to remove surface grease and organic matter, then use deionized water, acetone, and isopropanol to ultrasonically clean for 15 minutes each, blow dry with nitrogen, and use after being treated with ozone plasma for 20 minutes.
[0040] On the treated ITO conductive glass, a hole transport layer 2 is deposited by solution spin coating. The hole transport layer 2 is a P3CT-Cs material layer, which is formed by spin coating a methanol solution of P3CT-Cs with a concentration of 0.5 mg / ml, with a spin coater speed of 4000 rpm, a time of 30 seconds, and a thickness of 8 nm.
[0041] The tin-lead perovskite film 3 is prepared on the hole transport layer 2, and the specific method is as follows:
[0042] Tin-lead perovskite precursor solution: 1.20 mmol FAI, 0.30 mmol CsI, 0.75 mmol SnI2, 0.75 mmol PbI2 and 0.02 mmol GuaSCN were dissolved in a mixed solvent of 600 μl N,N-dimethylamine and 200 μl dimethyl sulfoxide, 20 mg metal lead powder was added, and stirred at room temperature overnight;
[0043] The tin-lead perovskite precursor solution was deposited on the P3CT-Cs hole transport layer by solution spin coating, with the rotation speed first at 1000 rpm for 5 seconds and then at 4000 rpm for 50 seconds, and 300 μL of chlorobenzene antisolvent was dropped at the end of the second rotation speed at the 5th second;
[0044] Then anneal at 130 °C for 5 minutes to form a tin-lead perovskite film;
[0045] The tin-lead perovskite film is post-treated by spin coating a 1.0 mg / ml lead fluoride isopropanol solution on the tin-lead perovskite film at a speed of 4000-5000 rpm for 20-30 seconds, and then annealing at 90-100 °C for 3-5 minutes;
[0046] An electron transport layer 5 is formed on the post-treated tin-lead perovskite thin film layer 4, a C60 layer with a thickness of 30 nm is deposited by vacuum evaporation, and then a BCP layer with a thickness of 6 nm is deposited on the C60 layer by vacuum evaporation, and a LiF layer with a thickness of 1 nm is deposited on the BCP layer by vacuum evaporation;
[0047] A layer of silver is deposited on the electron transport layer by vacuum evaporation as electrode 6 with a thickness of 100 nm. Figure 1 , a schematic diagram of the structure of a stannous fluoride-free tin-lead perovskite solar cell.
[0048] Figure 2The thermal stability schematic diagram of the perovskite film containing stannous fluoride additive and lead fluoride passivator of the present invention. In the figure, (a) is the thermogravimetric spectrum of iodoformamidine, the mixture of iodoformamidine and stannous fluoride, and the mixture of iodoformamidine and lead fluoride; (b) is the scanning electron microscope morphology of the perovskite film containing stannous fluoride additive and lead fluoride passivator degraded at 85°C for one week; (c) and (d) are the proportion of deprotonated N (N 1s XPS spectrum) of the perovskite film containing stannous fluoride additive and lead fluoride passivator before degradation and after degradation at 85°C for one week, respectively.
[0049] Figure 3 The schematic diagram of the change of the energy band structure of the perovskite film containing stannous fluoride additive and lead fluoride passivator before and after degradation of the present invention. (a)-(c) are the energy band structures of the surface (a) and bulk (b) of the perovskite film containing stannous fluoride before degradation and after degradation at 85°C for one week (c); (d)-(f) are the energy band structures of the surface (d) and bulk (e) of the perovskite film containing lead fluoride passivator before degradation and after degradation at 85°C for one week (f).
[0050] Figure 4 Schematic diagram of carrier transport performance of tin-lead perovskite battery of the control group, tin-fluoride additive, and lead fluoride passivator of the present invention. (a) is the fluorescence quantum yield of the tin-lead perovskite battery of the control group, tin-fluoride additive, and lead fluoride passivator; (b)-(c) are the transient absorption spectra of the tin-lead perovskite battery of the control group (b), tin-fluoride additive (c), and lead fluoride passivator (d).
[0051] Figure 5 The IV curve and photothermal stability diagram of the tin-lead perovskite battery of the control group and the tin-lead perovskite battery with the lead fluoride passivator of the present invention. (a) is the IV curve of the tin-lead perovskite battery of the control group and the tin-lead perovskite battery with the lead fluoride passivator; (b) is the external quantum efficiency of the tin-lead perovskite battery containing the lead fluoride passivator; (c)-(d) are the maximum power output stability of the tin-lead perovskite battery containing the lead fluoride passivator under continuous illumination at 65°C (c) and 85°C (d).
Claims
1. A method for preparing a tin-lead perovskite solar cell without stannous fluoride, characterized in that: The preparation method comprises the following steps: Step 1: Select a substrate, first use a cleaning agent to ultrasonically clean it for 10-30 minutes to remove surface grease and organic matter, then use deionized water, acetone, and isopropanol to ultrasonically clean it for 10-30 minutes each, blow dry it with nitrogen, and then treat it with ozone plasma for 15-30 minutes before use; Step 2: On the treated substrate, a hole transport layer is deposited by solution spin coating. The hole transport layer is a P3CT-Cs material layer, which is formed by spin coating a methanol solution of P3CT-Cs with a concentration of 0.2-1.0 mg / ml. The speed of the coating machine is 2000-5000 rpm, the time is 30-60 seconds, and the thickness is 5-10 nm. Step 3: Preparing a tin-lead perovskite thin film layer on the hole transport layer, specifically: 3.1: Prepare the tin-lead perovskite precursor solution: dissolve 1.20-1.30 mmol FAI, 0.30-0.45 mmol CsI, 0.75-0.90 mmol SnI2, 0.75-0.90 mmol PbI2 and 0.02-0.05 mmol GuaSCN in a mixed solvent of 600 μl N,N-dimethylamine and 200 μl dimethyl sulfoxide, add 20-60 mg metal lead powder, and stir at room temperature overnight; 3.2: Deposit the tin-lead perovskite precursor solution on the P3CT-Cs hole transport layer by solution spin coating, with the rotation speed first being 800-1500 rpm for 5-15 seconds, then 3500-5000 rpm for 40-70 seconds, and dropping 200-400 μL of chlorobenzene antisolvent between 5-10 seconds after the second rotation speed ends; Then annealing at 110-130°C for 10-15 minutes to form a tin-lead perovskite film; 3.3 The tin-lead perovskite film is subjected to surface passivation post-treatment, wherein a 0.5-1.5 mg / ml anhydrous isopropanol solution of a metal lead salt surface passivator is deposited on the tin-lead perovskite film by spin coating at a rotation speed of 4000-5000 rpm for 20-30 seconds, and then annealed at 90-100°C for 3-5 minutes; the metal lead salt is one of lead fluoride, lead bromide, lead chloride and lead oxalate; Step 4: an electron transport layer is formed on the post-treated tin-lead perovskite thin film layer, a C60 layer with a thickness of 20-40 nm is deposited by vacuum evaporation, and then a BCP layer with a thickness of 5-8 nm is deposited on the C60 layer by vacuum evaporation, and a LiF layer with a thickness of 1-3 nm is deposited on the BCP layer by vacuum evaporation; Step 5: depositing a layer of silver as an electrode on the electron transport layer by vacuum evaporation, with a thickness of 80-150 nm; and obtaining the tin-lead perovskite solar cell without stannous fluoride.
2. A tin-lead perovskite solar cell without stannous fluoride prepared by the method according to claim 1.
3. The tin-lead perovskite solar cell without stannous fluoride according to claim 1, characterized in that: The tin-lead perovskite film layer does not contain stannous fluoride additives, and reduces film defects and improves carrier extraction rate through chemical passivation and field effect passivation of the surface passivator; the surface passivator forms stable ionic bonds and interface dipole effects with the surface of the tin-lead perovskite film, ensuring the durability of the battery under light and heat conditions.
Citation Information
Patent Citations
Production method of high-temperature superconductive REBCO film
CN106242553A
Perovskite solar cell and preparation method thereof
CN113782678A
Tin-lead perovskite solar cell with uniform components and preparation method
CN116744763A
Surface-polished tin-lead perovskite solar cell and preparation method thereof
CN117979789A
Perovskite thin film, seed crystal-assisted film forming method, and perovskite solar cell
WO2024031752A1